The Automation System For The Production Of Materials, Semifinished Products And Finished Products In Logistics Production Processes - Faryha, R.; Chala, O. (ХНУРЕ, 2025)
This paper considers the development of an automation system for the production of materials, semi-finished products and finished products in logistics production processes. The proposed system improves control and management of resources, increasing the efficiency of logistics operations. Modern automation approaches are used, including integration with ERP systems and the use of IoT solutions.
Keywords: Industry 4.0; robotics; production processes; control and management of resources